Transcriptome and metabolome analyses of cold and darkness-induced pellicle cysts of Scrippsiella trochoidea - Guo, Xin (BMC Genomics, 2021)
BACKGROUND: Dinoflagellates are a group of unicellular organisms that are a major component of aquatic eukaryotes and important contributors to marine primary production. Nevertheless, many dinoflagellates are considered harmful algal bloom (HAB) species due to their detrimental environmental and human health impacts. Cyst formation is widely perceived as an adaptive strategy of cyst-forming dinoflagellates in response to adverse environmental conditions. Dinoflagellate cysts play critical roles in bloom dynamics. However, our insight into the underlying molecular basis of encystment is still limited. To investigate the molecular processes regulating encystment in dinoflagellates, transcriptome and metabolome investigations were performed on cold and darkness-induced pellicle cysts of Scrippsiella trochoidea. RESULTS: No significant transcriptional response was observed at 2 h; however, massive transcriptome and metabolome reprogramming occurred at 5 h and in pellicle cysts. The gene-to-metabolite network demonstrated that the initial transformation from vegetative cells into pellicle cysts was highly energy demanding through the activation of catabolism, including glycolysis, β-oxidation, TCA cycle and oxidative phosphorylation, to cope with cold-darkness-induced stress. However, after transformation into pellicle cysts, the metabolism was greatly reduced, and various sugars, polyunsaturated fatty acids and amino acids accumulated to prolong survival. The identification of 56 differentially expressed genes (DEGs) related to signal transduction indicated that S. trochoidea received a cold-darkness signal that activated multiple signal transduction pathways, leading to encystment. The elevated expression of genes encoding enzymes involved in ROS stress suggested that pellicle cysts respond to increased oxidative stress. Several cell cycle-related genes were repressed. Intriguingly, 11 DEGs associated with sexual reproduction suggested that pellicle cysts (or some portion thereof) may be a product of sexual reproduction. CONCLUSIONS: This study provides the first transcriptome and metabolome analyses conducted during the encystment of S. trochoidea, an event that requires complex regulatory mechanisms and impacts on population dynamics. The results reveal comprehensive molecular regulatory processes underlying life cycle regulation in dinoflagellates involving signal transduction, gene expression and metabolite profile, which will improve our ability to understand and monitor dinoflagellate blooms. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-021-07840-7.